2005
DOI: 10.1002/chin.200529293
|View full text |Cite
|
Sign up to set email alerts
|

Why Enzymes Are Proficient Catalysts: Beyond the Pauling Paradigm

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(90 citation statements)
references
References 1 publication
2
88
0
Order By: Relevance
“…The lowest reaction barrier is largely determined by the active-site electrostatic environment, which is constituted by the achieved transition-state configuration. Various theoretical models were proposed and a series of review articles were recently published [46,[50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest reaction barrier is largely determined by the active-site electrostatic environment, which is constituted by the achieved transition-state configuration. Various theoretical models were proposed and a series of review articles were recently published [46,[50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…We note that nucleophilic covalent catalysis is the most dominant form of covalent catalysis, with electrophilic second, and only a single entry in which homolytic methods are employed. It has been reported that partially covalent catalysis occurs in enzymes 29 and in MACiE we have chosen to classify such partial covalent/ionic bonds under proton shuttling or electrostatic stabilisation, as a consequence of the structure of MACiE annotations.…”
Section: Functions Performed By Amino Acid Residues During Catalysismentioning
confidence: 99%
“…Enzymes can be viewed as cellular tools to control and regulate the concentrations of certain molecules. The enthalpic barrier generally reported in the literature varies from 15 to 40 kcal/mol for different proteins (25). In solid state physics, the magnetization of 50-100 nm sized grains may be reversed by overcoming an energy barrier (26,27).…”
Section: Figurementioning
confidence: 99%